Pengembangan E-book melalui Game Interaktif Berbasis Aplikasi Canva untuk Meningkatkan Keterampilan Berbicara Bahasa Arab Siswa Kelas XI MA Tarbiyatut Tholibin Bumijawa Tegal - Fadila, Salma Nailul; Aisa, Aufia; Rahmawati, Rina Dian (YASIN, 2025)
The limited number of studies on the development of innovative learning media to enhance students’ speaking skills remains a challenge in Arabic language education, despite the significant impact of this skill on the overall quality of the teaching and learning process. This study aims to develop and evaluate the effectiveness of a game-based interactive e-book using the Canva application as a learning medium to improve the speaking skills of Grade XI students at MA Tarbiyatut Tholibin Bumijawa, Tegal. The research employed a Research and Development (R&D) method using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were Grade XI students, with data collected through interviews, questionnaires, observations, and pre-test and post-test assessments. The test instruments were analyzed for item difficulty and deemed appropriate. Validation results indicate that the learning media is highly valid, with scores of 92.5% from content experts and 87.5% from media experts, and highly feasible according to student evaluations (90.1%). Effectiveness testing using the Paired Sample t-Test (p < 0.05) and an N-Gain score of 76.6% demonstrated a significant improvement in students' speaking skills. These results support the effectiveness of Canva-based interactive e-books in Arabic language learning. The findings contribute theoretically to the literature on educational technology development and offer practical recommendations for teachers to adopt similar media to enhance learning quality. This study also opens opportunities for further exploration across different subjects and educational levels.